Successful use of CPAP in a pregnant patient with COVID-19 pneumonia - Reindorf, Maxine (BMJ Case Rep, 2021)
A 35-year-old nurse, who was 27 weeks pregnant at the time, was admitted to hospital with a short history of cough, fever and worsening shortness of breath. Oral and nasopharyngeal swabs were positive for SARS-CoV-2 on real-time viral PCR. During her admission, her breathing further deteriorated and she developed type 1 respiratory failure. A decision was made to trial treatment with continuous positive airway pressure (CPAP) as a means of avoiding intubation. The patient tolerated this well and made rapid improvements on this therapy. She was quickly weaned off and fully recovered before being discharged home. This case highlights the potential for CPAP to be used as a means of avoiding mechanical ventilation and iatrogenic preterm birth in COVID-19 pneumonia in pregnancy. Furthermore, it highlights the need for robust evidence to support this treatment.